Teachers' occupational well-being during the COVID-19 pandemic: The role of resources and demands. (September 2022) - Stang-Rabrig, Justine; Brüggemann, Thomas; Lorenz, Ramona; McElvany, Nele
Abstract: During the COVID-19 pandemic, teachers suddenly faced multiple challenges related to closed schools and remote teaching. This study investigated teachers' occupational well-being (stress, exhaustion, job satisfaction) and its relation to job resources (e.g., support from colleagues), job demands (e.g., technical difficulties), and personal resources (e.g., self-efficacy with digital media). 3250 teachers (82.8% female, M age  = 40.16) throughout Germany answered an online survey on resources, demands, and occupational well-being. The resource support from colleagues was particularly positively related to job satisfaction and negatively to stress and exhaustion. The results pattern remained mostly stable after including personal resources in the model. Highlights: During the COVID-19 pandemic, teachers were satisfied with their job on average. Female teachers were more stressed and exhausted on average than their male colleagues. The job resources support from colleagues and principal were both positively related to job satisfaction. The job demand hindrances was positively associated with perceived stress and exhaustion. The personal resource readiness to innovate positively related to job satisfaction, s elf-efficacy negatively to exhaustion .